Making molecules in cavity - Cederbaum, Lorenz S.; Fedyk, Jacqueline (The journal of chemical physics, 2024)
Free molecules undergo processes with photons; in particular, they can undergo photoionization and photodissociation, which are relevant processes in nature and laboratory. Recently, it has been shown that in a cavity, the reverse process of photoionization, namely, electron capture becomes highly probable. The underlying mechanism is the formation of a hybrid resonance state. In this work, we demonstrate that the idea of enhanced reverse processes is more general. We discuss the case of the reverse process of photodissociation, namely, making a molecule out of separate atoms in a cavity. For bound electronic states, the interaction of atoms and molecules with quantum light as realized in cavities is known to give rise to the formation of hybrid light-matter states (usually called polaritons). In the scenarios discussed here, the hybrid light-matter states are resonance (metastable) states, which decay into the continuum of either electrons or of the fragments of a molecule. Resonances can substantially enhance the outcome of processes. In addition to the new resonant mechanism of molecule formation, the impact of the hybrid resonances on the scattering cross section of the atoms can be dramatic.
Gesehen am 18.09.2024